Effect of Ripening Stimulant Types on Barangan Banana (Musa paradisiaca - Ali Murtadha; Elisa Julianti; Ismed Suhaidi (Universitas Sumatera Utara, 2013)
The present study is aimed at investigating the effect of different types of ripening stimulants on the quality of barangan banana. The experiment was conducted using complete randomized design consisting of two factors: the maturity stage of barangan banana i.e. M1 = 75-80% maturity stage, and M2 = 85-90% maturity stage, and the types of ripening stimulant i.e. P1 = Ethephon 250 ppm, P2 = Ethylene gas 250 ppm ,P3 = Acetylene gas 250 ppm, P4 = Calcium carbide 0.5% (5 g/kg banana fruit). The results showed the ripening stimulants did not ripen immature bananas (75-80% maturity stage) completely in terms of skin color development and softening rate. The effect on fruit ripening was indicated by increased color score and total soluble solids and decreased fruit hardness. Barangan banana at 85-90% maturity stage and treated with ethylene gas has the highest of color score and total soluble solid and the lowest of fruit hardness.